2016
DOI: 10.1016/j.bbr.2016.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of fibroblast growth factor 22 (FGF22) causes a depression-like phenotype in adult mice

Abstract: Specific growth factors induce formation and differentiation of excitatory and inhibitory synapses, and are essential for brain development and function. Fibroblast growth factor 22 (FGF22) is important for specifying excitatory synapses during development, including in the hippocampus. Mice with a genetic deletion of FGF22 (FGF22KO) during development subsequently have fewer hippocampal excitatory synapses in adulthood. As a result, FGF22KO mice are resistant to epileptic seizure induction. In addition to pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 44 publications
(54 reference statements)
0
24
0
Order By: Relevance
“…The effect of FGF9 was found to be opposite that of FGF2, which may be due to the inverse relationship between FGF9 expression and FGF2 expression, and FGF2 and FGF9 may act as physiological antagonists to mediate emotionality and vulnerability in mood disorders (Aurbach et al, 2015). FGF22 is expressed mainly in the skin and brain, and the deletion of endogenous FGF22 induced depression-like behavior, as shown by the FST, TST, and SPT (Williams et al, 2016). Recent studies have reported that FGF21 possesses various pharmacological activities including its antioxidant activity, suppression of apoptosis induced by endoplasmic reticulum stress (Liang et al, 2017), and anti-inflammatory activity Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…The effect of FGF9 was found to be opposite that of FGF2, which may be due to the inverse relationship between FGF9 expression and FGF2 expression, and FGF2 and FGF9 may act as physiological antagonists to mediate emotionality and vulnerability in mood disorders (Aurbach et al, 2015). FGF22 is expressed mainly in the skin and brain, and the deletion of endogenous FGF22 induced depression-like behavior, as shown by the FST, TST, and SPT (Williams et al, 2016). Recent studies have reported that FGF21 possesses various pharmacological activities including its antioxidant activity, suppression of apoptosis induced by endoplasmic reticulum stress (Liang et al, 2017), and anti-inflammatory activity Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…So far, research on the relationship between depression and FGF22 is still limited. The existing research on FGF22KO mice showed the undevelopment of excitatory synapses in the hippocampus, which could make explanation for the depressive behaviors . Previous animal studies on the FGF gene knockout mice showed that FGF2KO mice could exhibit depression‐like behaviors, and corresponding clinical studies conducted by Shen showed that the serum FGF2 levels were lower in depressive patients than in healthy controls .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Terauchi showed that FGF22KO mice failed to form excitatory synapses in the hippocampus during development . Williams further found that FGF22KO mice exhibited an increased time of immobility, increased floating time, and reduced preference for sucrose, which suggested that the pathogenesis of depression involves a decrease in FGF22. These studies provide converging, complementary proof for the role of FGF22 in the rodent brain, and FGF22 as a new depression‐related neurotrophic factor, the mechanism of which is gradually being revealed in depressive disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Igf2 -/- mice are resistant to acquiring epileptiform events in response to kainate administration ( Dikkes et al, 2007 ). Interestingly, Fgf22 -/- mice show seizure resistant phenotype ( Terauchi et al, 2010 ) and depression-like behavior ( Williams et al, 2016 ). Thus, defects in synapse stabilization through the FGF22–IGF2 pathway may be involved in diseases like epilepsy and depression.…”
Section: Discussionmentioning
confidence: 99%